Computational and characterization studies of non- conjugated poly (N-vinylcarbazole) blends as host polymer for phosphorescence emission / Ahmad Nazib Alias - Alias, Ahmad Nazib (Institute of Graduate Studies, UiTM, 2015)
Polarized absorption, optical dielectric spectra, absorption excitation and emissions spectra of blended poly (N-carbazole) (PVK) with poly(vinylidene fluoride-co-hexafluoropropene) (PVDFHFP) and polyvinylpyrrolidone (PVP) in the same composition have been investigated. The electronic structure has been calculated using extrapolation of oligomer method by semiempirical Zerner Modified Intermediate Neglect of Differential Overlap (ZINDO) calculation. Polymer coating was carried out using doctor blade technique on a quartz substrate. Polarized absorption, optical dielectric spectra, absorption excitation and emission spectra reveal that there are significant different results obtained between PVK, PVK:PVP and PVK:PVDF-HFP. The electronic parameters such as absorption edge (Ee), allowed direct bandgap (Ed), allowed indirect bandgap (Ei) and Urbach edge (Eu) were calculated using Tauc/ Davis-Mott Model. The dispersion behavior of polymer blending has been discussed using the Wemple–DiDomenico and Sellmeier model...